The Importance of Validity and Reliability in Research - Ina Maryana; Gina Tuty Alawiyah (al-Afkar, Journal For Islamic Studies, 2025)
Research is inseparable from research instruments. A good instrument is one that is valid and reliable. Validity means the instrument can be used to measure what it is supposed to measure. Validity refers to how well a test or tool measures what it is supposed to measure. Reliability refers to the extent to which the results of a measurement can be trusted. Validity and reliability are two crucial concepts that determine the quality of a measurement instrument. The purpose of this study was to determine the importance of validity and reliability in research for decision-making. This research method used library research from various materials such as reference books, previous similar research results, articles, and notes related to validity and reliability. The results showed that validity and reliability play a crucial role in research: improving the integrity of research results, ensuring proper data interpretation, being essential for decision-making based on research results, increasing confidence in research results, and without reliability, validity becomes questionable.